Contemporary Perspectives on Religions in Africa and the African Diaspora
IX, 285 p.
Keywords: Contemporary Perspectives on Religions in Africa and the African Diaspora explores African derived religions in a globalized world. The volume focuses on the continent, on African identity in globalization, and on African religion in cultural change.